Systematic review with meta‐analysis: the critical role of dermatological events in patients with hepatocellular carcinoma treated with sorafenib. Issue 5 (29th January 2019) - Díaz‐González, Álvaro; Sanduzzi‐Zamparelli, Marco; Sapena, Víctor; Torres, Ferran; LLarch, Neus; Iserte, Gemma; Forner, Alejandro; da Fonseca, Leonardo; Ríos, José; Bruix, Jordi; Reig, María
Summary: Background: The positive results of the REFLECT trial in terms of survival (sorafenib vs lenvatinib) offer a new first‐line option for hepatocellular carcinoma. Additionally, the expected results of immunotherapy could change the first‐line treatment in hepatocellular carcinoma or the clinical trial design in first and second‐line. Aims: To evaluate the impact of dermatologic adverse events under sorafenib in hepatocellular carcinoma patients as a clinical marker to predict prognosis and critically evaluate outcomes within trials. Methods: A systematic search of original articles published until October 2018 was performed using PubMed/MEDLINE and a meta‐analysis was performed according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement. Results: A total of 393 studies were identified and 13 articles with 2035 patients (79.5% Child‐Pugh‐A, 73.2% BCLC‐C) were selected for qualitative and quantitative analysis. The main type of dermatologic adverse events was hand‐foot skin reaction (47.7%) but other dermatologic adverse events were reported in 31.7% of the cases. Presence of dermatologic adverse events was associated with a lower mortality when compared with those patients without them (pooled Hazard Ratio for the univariate analysis 0.45 (95% CI: 0.38‐0.53) and there was no heterogeneity for the analysis ( P  = 0.511; I 2  = 0.0%). Refuting this association would require the future report of 1370 negative studies. Conclusions: This meta‐analysis shows a clinically meaningful association between dermatologic adverse events and a higher probability of longer survival. These data support the use of dermatologic adverse events in the clinical decision‐making when informing the prognosis and when systemic treatment is decided. Abstract : LINKED CONTENT This article is linked to Li et al and Sanduzzi‐Zamparelli et al papers. To view these articles, visit https://doi.org/10.1111/apt.15567 and https://doi.org/10.1111/apt.15572 .